Azimuthal decorrelation of jets widely separated in rapidity in pp collisions at s?=7s=7 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
The decorrelation in the azimuthal angle between the most forward and the most backward jets (Mueller-Navelet jets) is measured in data collected in pp collisions with the CMS detector at the LHC at root s = 7 TeV. The measurement is presented in the form of distributions of azimuthal-angle differences, Delta phi, between the Mueller-Navelet jets, the average cosines of (pi - Delta phi), 2(pi - Delta phi), and 3(pi - Delta phi), and ratios of these cosines. The jets are required to have transverse momenta, p(T), in excess of 35 GeV and rapidities, |y|, of less than 4.7. The results are presented as a function of the rapidity separation, Delta y, between the Mueller-Navelet jets, reaching Delta y up to 9.4 for the first time. The results are compared to predictions of various Monte Carlo event generators and to analytical predictions based on the DGLAP and BFKL parton evolution schemes.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Azimuthal decorrelation of jets widely separated in rapidity in pp collisions at root s=7 TeV. Journal of High Energy Physics(8), 41. doi:10.1007/jhep08(2016)139
Keywords: Hadron-Hadron Scattering (Experiments); Proton-Proton Scattering; Forward Physics; Jets; Particle Correlations And Fluctuations; Inelastic Ep Scattering